2009
DOI: 10.1029/2007gb003176
|View full text |Cite
|
Sign up to set email alerts
|

Carbon cycling under 300 years of land use change: Importance of the secondary vegetation sink

Abstract: [1] We have developed a dynamic land model (LM3V) able to simulate ecosystem dynamics and exchanges of water, energy, and CO 2 between land and atmosphere. LM3V is specifically designed to address the consequences of land use and land management changes including cropland and pasture dynamics, shifting cultivation, logging, fire, and resulting patterns of secondary regrowth. Here we analyze the behavior of LM3V, forced with the output from the Geophysical Fluid Dynamics Laboratory (GFDL) atmospheric model AM2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
397
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 379 publications
(433 citation statements)
references
References 72 publications
(134 reference statements)
19
397
1
Order By: Relevance
“…Previous studies have demonstrated the utility of historical gridded land-use-transition estimates for use in regional-global carbon/climate modeling studies Hurtt et al 2002;Roy et al 2003;Shevliakova et al 2009). Land-use transitions not only create important changes to ecosystems (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated the utility of historical gridded land-use-transition estimates for use in regional-global carbon/climate modeling studies Hurtt et al 2002;Roy et al 2003;Shevliakova et al 2009). Land-use transitions not only create important changes to ecosystems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulatively, land-use emissions of carbon to date are comparable to fossil fuel emissions (Houghton 1999). Land-use changes have altered the surface albedo, surface aerodynamic roughness, and rooting depth and terrestrial carbon balance, with resulting effects on regional-global weather, hydrology and climate (Pielke et al 2002;Roy et al 2003;Brovkin et al 2004;D'Almeida et al 2007;Piao et al 2007;Piao et al 2009;Pitman et al 2009;Shevliakova et al 2009;Pongratz et al 2010;Betts et al 2007). Habitat loss is the primary cause of species extinctions (UNEP 2002;Mace et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lal (2004) estimates that cultivation has caused the loss of 78 ± 12 PgC from soils since 1850. Modeling studies suggest that LULCC can contribute a net loss of soil carbon globally, from ∼ 13 % of total LULCC carbon emitted (Strassmann et al, 2008) to ∼ 37 % (Shevliakova et al, 2009), or a net gain as in Arora and Boer (2010). Recently, Levis et al (2014) implemented a cultivation parameterization that includes impacts on soil carbon and found an additional global flux of 0.4 PgC yr −1 from soils due to crop management in recent decades.…”
Section: Co 2 Emissionsmentioning
confidence: 99%
“…The most common allocation approach assigns C to each plant component (usually leaf, stem, and root) via fixed ratios that vary with plant functional type (PFT), but not spatially or temporally [38,85,88,95,107,[113][114][115]. For models that include N (and less often P), N uptake plays a strong role in governing C assimilation and drives competition between plants and decomposers.…”
Section: Allometrymentioning
confidence: 99%